A Horse Called Mayonnaise - Nowack, JoAnne Chitwood; Nang Chan Yeema (Hagerstown, Maryland, United States Review and Herald Publishing Association, 1995)
Ever since Tory heard about the horseback trip at camp, she'd been unable to think of anything else. But now her dream is in trouble. Gorgeous Jan Cole has signed up to go, and only tow girls will be chosen. How can she compete against a girl who always seems to get everything based on her good looks? Discouraged, Tory's ready to quit till a friend helps her see herself from God's point of view. When she decides to trust Him, she's in for a summer beyond her wildest dream. A summer that brings the thrill of a horse called Mayonnaise.
Keywords: Adult Fiction